Armed E-Bunny - Debbabi, Mourad (2017)
This paper presents a new selective dynamic compilation technique targeting ARM 16/32-bit embedded system processors. This compiler is built inside the J2ME/CLDC (Java 2 Micro Edition for Connected Limited Device Configuration) platform [8]. The primary objective of our work is to come up with an efficient, lightweight and low-footprint accelerated Java virtual machine ready to be executed on embedded machines. This is achieved by implementing a selective ARM dynamic compiler called Armed E-Bunny into Sun's Kilobyte Virtual Machine (KVM) [9]. In this paper, we present the motivations, the requirements, the architecture, the design, the implementation and debugging issues of Armed E-Bunny. The modified KVM is ported on an Embedded-Linux PDA and is tested using standard J2ME benchmarks. The experimental results on its performance demonstrate that a speedup of 360% over the last version of Sun's KVM is accomplished with a footprint overhead that does not exceed 119KB.